Pengaruh Literasi Keuangan, Pendidikan Keuangan Keluarga, Sikap Keuangan, dan Teman Sebaya Terhadap Perilaku Keuangan Mahasiswa - Maylizza Putri Dyansyah; Maria Yovita R. Pandin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study is to identify variables that influence financial behavior among S1 Accounting students in Surabaya. These variables include financial literacy, family financial education, financial attitudes, and peer influence. Questionnaires serve as the primary data collection tool for this quantitative study. This sampling method is based on Roscoe's Purposive Sampling theory and strategy. This study analyzed data using SEM-PLS. The findings revealed that there was a positive and statistically significant association between financial behavior and financial literacy, financial attitudes and peers, and no association between financial behavior and family financial education.